LEARNERS’ CORE COMPETENCY DEVELOPMENT IN HEALTH AND PHYSICAL EDUCATION DEPARTMENT - Banlusook, Anuwat (Academic Journal Phranakhon Rajabhat University, 2022)
Competency is person’s ability for using knowledge, skills, and variety of one’s attitudes as well as characteristics in working or problem-solving success. Competency can be perceived through one’s behavior which is able to measure and evaluate. Competency is the sum of knowledge, skills, attributes, characteristics and other abilities which can lead to professional success. The development of learners ‘core competence in learning management of Health and Physical Education Department is crucial for learners’ preparation in the 21st century. Teachers can choose six guidelines of learning management for learners’ core competence development according to their own proficiency and appropriateness of context. Those guidelines are 1) using the original work by enhancing competency, 2) using original work by adding competency, 3) using learning model through competency development, 4) competency-based by integrating the indicators, 5) integrating and coordinating various competencies, and 6) life competency in daily routine. Schools and teachers can design learning management which focus on developing knowledge, skills and attributes for learners’ abilities in learning, working and value creation of life, community and society.